Yield stability of six maize varieties and their respective intervarietal crosses - Lopes, Maurício Antônio; Gama, Elto Eugenio Gomes e; Magnavaca, Ricardo (Pesquisa Agropecuaria Brasileira, 2014)
Yields stability of six maize (Zea mays L.) varieties and their respective 15 intervarietal crosses were studied at different environments in eight states: São Paulo, Minas Gerais, Espírito Santo, Mato Grosso do Sul, Goiás, Paraná, Rio Grande do Sul and Acre. The varieties CMS 05 and CMS 04 showed the best performance "per se" and the best intervarietal crosses were CMS 05 x CMS 28, CMS 05 x CMS 04, CMS 12 x CMS 04, CMS 05x CMS 11, CMS 11 x CMS 28 and CMS 05 x CMS 12. All these above cultivars showed ample stability, measured by stability parameter (b), but, according to regression deviation (S2d) the cultivars CMS 05 x CMS 12, CMS 05 x CMS 04, CMS 12 x CMS 04, CMS 22 x CMS 28, CMS 04 x CMS 28 and CMS 22 showed significant deviations. The varietal cross CMS 05 x CMS 28 was the best in terms of stability.